2015
DOI: 10.1002/2014wr016422
|View full text |Cite
|
Sign up to set email alerts
|

Comparing drinking water treatment costs to source water protection costs using time series analysis

Abstract: We present a framework to compare water treatment costs to source water protection costs, an important knowledge gap for drinking water treatment plants (DWTPs). This trade‐off helps to determine what incentives a DWTP has to invest in natural infrastructure or pollution reduction in the watershed rather than pay for treatment on site. To illustrate, we use daily observations from 2007 to 2011 for the Bob McEwen Water Treatment Plant, Clermont County, Ohio, to understand the relationship between treatment cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 35 publications
2
56
2
Order By: Relevance
“…At the local level, high nutrient concentrations in agricultural runoff have increased the costs of drinking water treatment [Heberling et al, 2015] and, recently, have led to litigation calling for greater regulation of agricultural nutrient sources [Stowe, 2016]. At larger scales, nutrient loading to near-shore coastal waters has fed the growth of large hypoxic zones, decreasing marine biodiversity and altering ecosystem structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the local level, high nutrient concentrations in agricultural runoff have increased the costs of drinking water treatment [Heberling et al, 2015] and, recently, have led to litigation calling for greater regulation of agricultural nutrient sources [Stowe, 2016]. At larger scales, nutrient loading to near-shore coastal waters has fed the growth of large hypoxic zones, decreasing marine biodiversity and altering ecosystem structures.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last century, intensive agricultural practices and increasing fossil fuel consumption have led to high levels of nonpoint source nutrient pollution, threatening drinking water quality, and contributing to the destruction of aquatic ecosystems from the local to the global scale [Rockström et al, 2009;Howarth et al, 2011;Carpenter et al, 2012;Beusen et al, 2016]. At the local level, high nutrient concentrations in agricultural runoff have increased the costs of drinking water treatment [Heberling et al, 2015] and, recently, have led to litigation calling for greater regulation of agricultural nutrient sources [Stowe, 2016]. At larger scales, nutrient loading to near-shore coastal waters has fed the growth of large hypoxic zones, decreasing marine biodiversity and altering ecosystem structures.…”
Section: Introductionmentioning
confidence: 99%
“…Among recent US‐based studies, a 1% decline in TOC was associated with a 0.46 and 0.77% reduction in chemical costs (Warziniack et al , Freeman et al ). However, Heberling et al () found that TOC has no appreciable effect on variable costs. A 1% decline in nitrate concentrations, sediment loading, and phosphorus loading is associated with 0.02, 0.26, and 0.02–0.19% reductions in variable costs, respectively (Mosheim & Ribaudo , Heberling et al , McDonald & Shemie ).…”
Section: Review Of Research and Knowledge Gapsmentioning
confidence: 99%
“…Studies show that marginal improvements in source water quality lead to modest reductions in treatment costs. Evidence of this effect is most robust for turbidity, where recent US‐ and Canada‐based studies showed that a 1% decline in turbidity led to a 0.09–0.11% reduction in variable costs (Price et al , Heberling et al , Mosheim ). For example, with a $1 million annual‐treatment‐cost budget, a PWS could save $1,100 per year if a 1% reduction in turbidity led to a 0.11% change in treatment costs.…”
Section: Review Of Research and Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation